Overcurrent and earth fault relay setting and coordination using PSS-Adept / Musafri Abdullah Azmi - Abdullah Azmi, Musafri (2010)
This paper studies the protective relay setting and coordination using PSS-Adept. Faults and failures normally occur in power system. Power system needs an auxiliary system that must take corrective action on the occurrence of a fault. This auxiliary system is knows as protection system. Protection systems are sets of equipments to detect faults in the protected elements of the power systems, to disconnect the faulted element and to re-establish the service. This paper approach for over current and earth fault as protection system. Protective device coordination is the process of determining the best timing of current interruption when abnormal electrical conditions occur.